2019
DOI: 10.14807/ijmp.v10i3.892
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of greenhouse gases emissions disclosure according to GRI guidelines in Brazilian companies

Abstract: This study aimed to identify the determinant factors of greenhouse gases emissions disclosure in Brazilian companies. Therefore, a documental research was conducted, in which we analyzed sustainability reports, GRI-provided data and accounting statements of B3-listed companies that published sustainability reports and accounting statements for the year 2016. This is a descriptive research with quantitative approach. Preliminarily, we identified information about greenhouse gases emissions disclosed by the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The studies on GHG emissions are focused on differences in the type of disclosure among companies that must comply with mandatory regulations Leal et al (2019) They demonstrate that Brazilian companies have a low level of GHG emission disclosure…”
Section: Female Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on GHG emissions are focused on differences in the type of disclosure among companies that must comply with mandatory regulations Leal et al (2019) They demonstrate that Brazilian companies have a low level of GHG emission disclosure…”
Section: Female Representationmentioning
confidence: 99%
“…From there, we check whether companies have continued to publish reports and how long they have been in the program. The authors investigated whether the percentage of women on BOD and the gender of the CEO and CFO influence the results of European companies They did not find evidence that greater participation of women on BOD or the fact that the company had a female CEO or CFO contributes to reducing results management Leal et al (2019) They identified the determining factors for the disclosure of GHG emissions in Brazilian companies…”
Section: Female Representationmentioning
confidence: 99%
“…In addition to general reviews of GRI reporting, there has been extensive research into corporate compliance with GRI standards across a range of settings and topics (see, e.g. Leong et al, 2014;Egan et al, 2015;O'Neill et al, 2015;Leal et al, 2019;Parsa et al, 2019;Tello et al, 2019), which has typically reported poor results. Surprisingly, little research, however, has examined the quality of the GRI standards themselves, especially in relation to developing countries.…”
Section: Introductionmentioning
confidence: 99%